Effect of Interpersonal Relationships, Work Stress, and Work Environment on Employee Performance: The Mediating Role of Job Satisfaction - Rachmawati, Dewi Lailatul; Vivin Maharani Ekowati (Jurnal Ilmiah Sumber Daya Manusia, 2025)
In the era of globalization and increasingly fierce business competition, organizations face pressure to maximize employee performance as a critical asset in achieving their business objectives. This research examines how interpersonal relationships, work stress also the work environment influence employee performance, with job satisfaction as a mediating aspect. The study employs a quantitative approach, using employees of Pertamina gas stations in Malang as the population and sample. A saturated sampling technique was used for sample selection, resulting in 33 respondents, with primary data collected for the research. SmartPLS 4 was utilized as the data analysis tool. The outcome reveal that interpersonal relationships have a significant positive impact on employee performance, whereas work stress and the work environment do not show a significant impact. Furthermore, the mediation of job satisfaction in the relationship between interpersonal connections and work stress on employee performance is insignificant. In contrast, the work environment does demonstrate a substantial positive influence. These results emphasize the necessity of fostering strong interpersonal relationships, managing stress effectively, and enhancing the work environment to boost employee performance.